The Meaningful Participation of ‘Stakeholders’ in Global Drug Policy Debates—A Policy Comment - Ann Fordham (Revue Internationale de Politique de Développement)
This policy comment seeks to address three key questions relating to the participation of civil society in international drug policymaking. Firstly, who are the relevant ‘stakeholders’ and what options do they have to participate in drug policy discussions at the United Nations level? Secondly, have certain ‘stakeholders’ been able to positively influence the direction of global drug policies? And thirdly, who are the ‘most affected’ communities and what could be done to improve their meaningful engagement in the definition of drug policies that directly impact their lives? Unpacking the terminology around civil society, stakeholders, and most affected communities, the chapter argues for a clearer distinction between ‘rights-holders’ and ‘duty-bearers’. Masking the inherent power imbalances between the different stakeholders risks underplaying the rights of affected communities and legitimising a place at the table for corporations as ‘equal actors’ in spite of fundamentally different interests. The commentary concludes that the increased involvement over the past decade of civil society as well as other United Nations entities around the 2016 United Nations General Assembly Special Session on the World Drug Problem (UNGASS) has markedly influenced the global drug policy debate by shifting more attention towards health, human rights and development concerns.